2023
DOI: 10.1111/tpj.16235
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of drought tolerance in Arabidopsis involves the PLATZ4‐mediated transcriptional repression of plasma membrane aquaporin PIP2;8

Abstract: SUMMARY Plant A/T‐rich protein and zinc‐binding protein (PLATZ) transcription factors play important roles in plant growth, development and abiotic stress responses. However, how PLATZ influences plant drought tolerance remains poorly understood. The present study showed that PLATZ4 increased drought tolerance in Arabidopsis thaliana by causing stomatal closure. Transcriptional profiling analysis revealed that PLATZ4 affected the expression of a set of genes involved in water and ion transport, antioxidant met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Among them, AT1g01550 and AT3g05090 have been suggested to be involved in plant growth by participating in auxin responses, 28 , 33 and AT3g73980, AT4g12700, AT4g30480, and AT2g16850 have been reported to be involved in abiotic stress response. 31 , 34–37 To identify the biological roles of their phosphorylation by MPKs, it is necessary to test whether the phenotypes of these knock-out mutants can be rescued by the expression of the non-phosphorylation form. In the case of unknown substrates (AT2g04235, AT2g21300, AT3g04470, AT3g19330, and AT4g18950), the biological function of them would be identified first, and then the biological function of their phosphorylation should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, AT1g01550 and AT3g05090 have been suggested to be involved in plant growth by participating in auxin responses, 28 , 33 and AT3g73980, AT4g12700, AT4g30480, and AT2g16850 have been reported to be involved in abiotic stress response. 31 , 34–37 To identify the biological roles of their phosphorylation by MPKs, it is necessary to test whether the phenotypes of these knock-out mutants can be rescued by the expression of the non-phosphorylation form. In the case of unknown substrates (AT2g04235, AT2g21300, AT3g04470, AT3g19330, and AT4g18950), the biological function of them would be identified first, and then the biological function of their phosphorylation should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The PLATZ transcription factor family plays an indispensable role in the growth and development of plants and their responses to abiotic stress. Several PLATZ family genes have been studied in Arabidopsis, maize, wheat and rice, with functions related to seed size (Wang et al, 2019; Zhou and Xue, 2019), endosperm formation (Li et al, 2017; Li et al, 2021), ROS regulation (Yamada et al, 2019), responses to high salt and drought stress (Liu et al, 2020; Liu et al, 2023), and hormone signaling pathways (Timilsina et al, 2022; Liu et al, 2023; Zhang et al, 2023). In this study, the rice OsPLATZ3 , belonging to the PLATZ gene family, is predominantly expressed in the tapetum during late anther development.…”
Section: Discussionmentioning
confidence: 99%
“…ORESARA15 ( ORE15 ) regulates the size of the root apical meristem (RAM) by balancing the actions of auxin and cytokinin signaling pathways (Timilsina et al, 2022). PLATZ4 enhances drought resistance by promoting stomatal closure and regulating genes associated with abscisic acid (ABA) signaling (Liu et al, 2023). In rice, the genes GL6 and SG6 belong to the PLATZ protein family and are involved in controlling the length and size of rice grain (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…AtPLATZ2 is involved in the regulation of stress tolerance as lines overexpressing AtPLATZ2 had an increased sensitivity to salt stress (Liu et al, 2020). AtPLATZ4 was found to promote drought tolerance by directly repressing Plasma membrane Intrinsic Protein 2;8 (PIP2;8) as well as by regulating genes involved in ABA signalling (Liu et al, 2023). In poplar, PtPLATZ1-4 and PtPLATZ8-9 are involved in cadmium tolerance as evidenced by heterologous expression in yeast and overexpression in poplar (Ma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ORE15 was reported to be a regulator of root growth and development as it positively controls root apical meristem size in a process involving auxin and cytokinin signalling-related pathways (Timilsina et al, 2022). Transgenic Arabidopsis overexpressing AtPLATZ4 exhibited a lower fresh weight than the WT, and it was suggested that AtPLATZ4 acts as a negative regulator of growth by suppressing the expression of EXP6 and EXP16 expansin genes thereby inhibiting the expansion of the cell wall (Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%